EFFECT OF ACIDITY, BASICITY, HETEROGENEOUS CaO/SILICA GEL CATALYST FROM BIOMASS WASTE ON BIODIESEL YIELD FROM CRUDE PALM OIL - Mulyani, Yenni; Nurhayati, Nurhayati; Awaluddin, Amir (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2024)
The global energy sector has been dominated by non-renewable fossil fuels, prompting many countries to invest in renewable energy sources such as biodiesel. Crude palm oil (CPO), as a biodiesel feedstock, has a high FFA content, which can cause saponification reactions. This can reduce the quality of biodiesel if only CaO catalyst is used. Therefore, acid catalysts such as silica gel are needed to overcome this problem. Silica gel can also improve the stability, reactivity, and effectiveness of CaO catalyst in biodiesel production. This study aims to synthesize and characterize the heterogeneous CaO/silica gel catalyst obtained from biomass waste, and evaluate its activity in the conversion of CPO into biodiesel. The CaO/silica gel hybrid catalyst was prepared by wet impregnation method with varying percentage of silica gel (5%, 10%, and 15%), which was synthesized from coconut husk using sol-gel method, and mixed with CaO from calcination of blood clam shells at 900°C for 5 hours. The basicity characterized using the acid-base titration method, while the acidity was analyzed using pyridine adsorption method with FTIR, and the surface area was analyzed by BET method. The results showed that the synthesis of CaO/silica gel was successful, with confirmation of FTIR data at specific wavelengths. The addition of silica gel increased the acidity and surface area and decreased the basicity of CaO catalyst, with 10% CaO/silica gel showing optimal acidity and surface area. Testing the catalyst activity in the reaction of biodiesel formation from CPO produced the highest biodiesel yield of 96.71% using CaO/silica gel 10%. The conclusion of this study is that biomass waste-based heterogeneous catalysts have high potential for biodiesel production, which is influenced by their acidity and surface basicity, and offer a low-cost and environmentally friendly solution.